Pengabdian Donor Darah Pada Masyarakat Di Kabupaten Sidoarjo Oleh PT Telkom Akses - Nailatun Nimah; Gendut Sukarno (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
Blood is a liquid that has a very important role in the human body, the existence of blood aims to distribute oxygen and nutrients to all body cells. But in reality, in Indonesia, the ideal blood stock, which should be 2% of the total population of Indonesia, is still far from enough, so it is necessary to have additional blood supply to reach the ideal count. Blood donation is one of the activities that can help this goal. In collaboration with PMI, PT Telkom Akses conducted community service through blood donation activities. In its implementation, 55 participants participated, with 30 people successfully donating blood and 25 people were unsuccessful because their hemoglobin (HB) levels did not meet the requirements. But overall this blood donation activity went well and smoothly.